Philosophy and policy, then and now: unfolding the Rural Tourism Policy perspectives in Malaysia - Siow, May Ling; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman (Global Journals, 2014)
The paper examines the evolution of political philosophers from the time of Plato (428 BC), Ibn Khaldun (1406) and Confucius (479 BC) to the current day political philosophers represented by John Dewey (1952) and Harold Lesswell (1978). The paper further examines how this departure has diluted philosophy from the policy making process, from what used to be an integration of philosophy and policy making to separating the philosophical component from it. This is seen as anissue in modern day policymaking as philosophy is legitimately concerned with the human affair and serves as guidance to humanity. Taking it into the Malaysian context, a snapshot of the Malaysian Ecotourism Plan will be used as an example to further illustrate the absence of philosophy in modern day policy making. This policy is important, as it serves as the backbone to the overall conservation of rural tourism in Malaysia.